ANALISIS PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUTUSAN MAHASISWA MEMILIH TEMPAT INDEKOS DENGAN HARGA SEWA INDEKOS SEBAGAI VARIABEL MODERASI - Kurniawan, Andre (Universitas Slamet Riyadi, 2015)
The purpose of this study was to analyze the significance of the influence of location, facilities and rental rates boarder partially on student decision choosing a boarder at the Village Panularan Laweyan District of the city of Surakarta. To analyze the effect of moderating the influence of homestay rental rates and facilities location to choose a student's decision boarder at the Village Panularan Laweyan District of the city of Surakarta. In conclusion, no significant influence on the decision of the location of the students choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. There was a significant effect of the facility to choose a student's decision boarder at the Village Panularan Laweyan District of the city of Surakarta. There was a significant influence on the decision of the rental price boarder students choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Lodger rental prices do not moderate influence on the decision of the location of the student choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Lodger rental prices do not moderate the effect of the facility to the decision of the student choose a boarder at the Village Panularan Laweyan District of the city of Surakarta. Keywords: location, facilities, rental prices lodger, students choose a lodger decision